Token ekonomi sebagai perlakuan menurunkan perilaku hiperaktif pada anak dengan attention deﬁcit hyperactivity disorder - Ulwiyatul Wia Hidayat (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
Attention Deﬁcit Hyperactivity Disorder (ADHD) is a behavior that can affect the others. In this case, the subject cannot sit quietly, running around, talk endlessly, cannot be queued, not focus and the pronunciation is not clear. Based on the problems experienced by the subject of today’s most troubling is hyperactive behavior, the subject is not able to sit quietly and often running around. It is reported by parents and the class teacher. Assessment methodswere interviews, observation and the Wechsler Adult Intelligence Scale. The intervention given to overcome these problems was token economy. The results of the intervention showed that the behavior of a hyperactive form of cannot sit quietly and often running around can be reduced.